2007
DOI: 10.1016/j.aquaculture.2007.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between oyster mortality patterns and environmental data from monitoring databases along the coasts of France

Abstract: Oyster mortality was monitored at multiple sites along the French coastline (5 500 km) between 1993 and 2005. Mortality data for one-and two-year-old oysters were collected over 10-12 years in 39 oyster culture sites bordering 3 different "seas": the English Channel, Bay of Biscaye and Mediterranean. Combining these data with records from environmental monitoring databases, 11 of these sites had consistent chronological data sets including both environmental data and mortality records. Mortality in one-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 20 publications
(23 reference statements)
1
61
0
1
Order By: Relevance
“…Indeed, as mortality events result from a combination of factors, in a different manner from one ecosystem to another, there is a need for site-specific investigations of environmental parameters to provide a better understanding of the summer mortality phenomenon (Soletchnik et al 2007). To this end, seawater temperature, salinity, rainfall, phytoplankton concentration and quality, and dissolved oxygen concentrations were analysed parallel to mortality monitoring.…”
Section: Abstract: Bivalves · Energetic Reserve · Environment · Fattmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as mortality events result from a combination of factors, in a different manner from one ecosystem to another, there is a need for site-specific investigations of environmental parameters to provide a better understanding of the summer mortality phenomenon (Soletchnik et al 2007). To this end, seawater temperature, salinity, rainfall, phytoplankton concentration and quality, and dissolved oxygen concentrations were analysed parallel to mortality monitoring.…”
Section: Abstract: Bivalves · Energetic Reserve · Environment · Fattmentioning
confidence: 99%
“…Mass mortalities of Crassostrea gigas have been reported in many areas of the world where this species is cultivated: in Japan (Mori 1979), the USA (Perdue et al 1981, Cheney et al 2000, Friedman et al 2005, Mexico (Luna-González et al 2009), and Western Europe (France: Soletchnik et al 2007, Germany: Watermann et al 2008 andIreland: Malham et al 2009). During spring-summer 2008, mass mortality of 1-yr-old C. gigas occurred simultaneously along all coasts of France.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first descriptions of an MMB outbreak dates to 1878, with the observation of bivalve diseases (Lafferty et al 2004). Mass (or abnormal) mortalities of bivalve populations are generally defined as a loss of > 30% of the stock (Soletchnik et al 2007, EFSA 2010). An increasing number of MMB outbreaks throughout the world has been reported since the 1960s (Imaï et al 1965, Harvell et al 1999, Lafferty et al 2004, Soletchnik et al 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Mass (or abnormal) mortalities of bivalve populations are generally defined as a loss of > 30% of the stock (Soletchnik et al 2007, EFSA 2010). An increasing number of MMB outbreaks throughout the world has been reported since the 1960s (Imaï et al 1965, Harvell et al 1999, Lafferty et al 2004, Soletchnik et al 2007). This increase can be explained as a result of research progress on identification of diseases, the intensification of bivalve aquaculture, or may reflect changes in environmental conditions in production areas caused by climate change and water pollution.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although the Portuguese oyster, C. angulata, was highly susceptible to this virus, C. gigas appeared resistant to this virus disease. In late 70ies and early 80ies, high mortalities (more that 50%) of Pacific oyster larvae have been reported in commercial hatcheries from Washington State in USA [6].The cause of C. gigas summer mortalities remained unclear, but studies suggested a complex etiology in which environmental and physiological conditions of the host (age/weight and sexual maturation) were involved [7,8].…”
Section: Introductionmentioning
confidence: 99%